2021
DOI: 10.1017/s0954579421000122
|View full text |Cite
|
Sign up to set email alerts
|

Marital quality over the life course and child well-being from childhood to early adolescence

Abstract: Research on marital quality and child well-being is currently limited by its common use of geographically constrained, homogenous, and often cross-sectional (or at least temporally limited) samples. We build upon previous work showing multiple trajectories of marital quality and data from the National Longitudinal Survey of Youth-1979 (NLSY79) regarding mothers and their children (inclusive of ages 5–14). We examine how indicators of child well-being are linked to parental trajectories of marital quality (happ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…These were crossed by each partner's responses, such that there were 16 possible rows of data each representing the possible combinations of partners in each of the four classes; combined weights across all rows summed to 1; rows with zero probability of class membership were removed. Thus, rather than weighting the data just by the most likely class, data were weighted and included for those that had a likelihood of being in any of the classes (Galovan et al, 2019; James et al, in press), and we used this data in cross‐tabulation analysis. Finally, we evaluated how the correlation between relationship satisfaction and relational‐connectivity differed by class.…”
Section: Methodsmentioning
confidence: 99%
“…These were crossed by each partner's responses, such that there were 16 possible rows of data each representing the possible combinations of partners in each of the four classes; combined weights across all rows summed to 1; rows with zero probability of class membership were removed. Thus, rather than weighting the data just by the most likely class, data were weighted and included for those that had a likelihood of being in any of the classes (Galovan et al, 2019; James et al, in press), and we used this data in cross‐tabulation analysis. Finally, we evaluated how the correlation between relationship satisfaction and relational‐connectivity differed by class.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding reverse causality, there is some evidence that poor physical health in children may result from family conflict, which could explain the increased parental separation risk even before the first diagnosis. Studies have shown that poor parental relationship quality has a detrimental effect on children's overall physical health, as rated by mothers (James et al 2022) and children themselves (Hair et al 2009). While Repetti et al (2002) also showed in a systematic literature review that family conflict often leads to poor physical health in children, they only used studies in which children's health was reported by the parents.…”
Section: Parental Separation Risk Preceding a Child Health Condition ...mentioning
confidence: 99%
“…We first conducted BCH analyses on the coupled and single profile solutions separately to examine profile differences on the outcome and indicators. For analyses where we wanted to compare coupled versus single profiles directly, we combined the class probabilities for both profile solutions, wherein the class probabilities from a given solution were kept while the class probabilities for the other solution were given a weight of zero (Galovan et al, 2022; James et al, 2022). In other words, individuals in coupled profiles would have a zero probability of being in any of the single profiles and vice versa.…”
Section: Analytic Planmentioning
confidence: 99%